DETEKSI Liberibacter spp. PADA JERUK SIAM BERGEJALA KLOROSIS DISERTAI BERCAK HITAM DENGAN Polymerase Chain Reaction - Iliana, Iliana; Rahmawati, Rahmawati; Rachmat, Agus; Mukarlina, Mukarlina; Zakaria, Latiffah (Universitas Tanjungpura, 2020)
Liberibacter bacteria are one of the pathogenic bacteria in citrus plants. Siam Citrus Plant in Setapok Village, Singkawang City, suspected to be infected with Liberibacter spp. bacteria by showing patterns of symptoms of chlorosis accompanied by patches. This study aims to detect Liberibacter spp. on Siam Citrus leaves with symptomatic chlorosis with patches. Leaf sampling uses the roaming method in one of the citrus plantations in Setapok Village, Singkawang City.Â Detection of Liberibacter spp. done by PCR (Polymerase Chain Reaction) technique. Detection of bacterial DNA through several stages namely, isolation of bacterial plasmid DNA, 16S rDNA gene amplification with a thermocycler machine, and visualization using a set of electrophoresis devices. Electrophoresis results show the presence of DNA band lines, with a size of around 1100 bp for OI1 and OI2c primers, and DNA bands of 703 bp for A2 and J5 specifics. The results showed that there were Liberibacter spp. in the symptomatic chlorosis of Siam Citrus leaves accompanied by patches.